2023
DOI: 10.3390/jcm12103521
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathic Traits, Externalizing Problems, and Prosocial Behavior: The Role of Social Dominance Orientation

Abstract: Psychopathic traits in community and referred youths are strongly associated with severe externalizing problems and low prosocial behavior. However, less is known about the mechanisms that may link youth psychopathy and these outcomes. Social dominance orientation (SDO), defined as the general individual orientation toward unequal and dominant/subordinate relationships, might represent a valuable construct to explore to better understand the association between psychopathic traits, externalizing problems, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Additional studies have found support for the four‐factor structure across investigations in Belgium (Colins et al, 2023), China (Luo et al, 2021), Iran (Elhami Athar et al, 2022; Elhami Athar et al, 2023), Italy (Muratori et al, 2021), Portugal (Ribeiro da Silva et al, 2023), and the United States (Salekin et al, 2022). Additionally, studies have found support for the reliability of the PSCD scale and its relation to theoretically meaningful correlates (Batky et al, 2020; Bontemps, Batky, Houser, & Salekin, 2022; Grossi et al, 2023; Luo et al, 2021; Muratori et al, 2021; Ribeiro da Silva et al, 2023). Specifically, the PSCD has been shown to correlate positively with alternate measures of psychopathy and to exhibit good discriminant validity and to relate to a variety of external correlates such as reaction to unfamiliar peers, proactive aggression, reactive aggression, substance use, and arrest history (e.g., Salekin et al, 2022).…”
Section: Introductionmentioning
confidence: 98%
“…Additional studies have found support for the four‐factor structure across investigations in Belgium (Colins et al, 2023), China (Luo et al, 2021), Iran (Elhami Athar et al, 2022; Elhami Athar et al, 2023), Italy (Muratori et al, 2021), Portugal (Ribeiro da Silva et al, 2023), and the United States (Salekin et al, 2022). Additionally, studies have found support for the reliability of the PSCD scale and its relation to theoretically meaningful correlates (Batky et al, 2020; Bontemps, Batky, Houser, & Salekin, 2022; Grossi et al, 2023; Luo et al, 2021; Muratori et al, 2021; Ribeiro da Silva et al, 2023). Specifically, the PSCD has been shown to correlate positively with alternate measures of psychopathy and to exhibit good discriminant validity and to relate to a variety of external correlates such as reaction to unfamiliar peers, proactive aggression, reactive aggression, substance use, and arrest history (e.g., Salekin et al, 2022).…”
Section: Introductionmentioning
confidence: 98%